Penerapan Model Pembelajaran Kooperatif Tipe CRH (Course, Review, Horray) Untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa SMP - Auliya, Risma Nurul; ., Darhim; Nurlaelah, Elah (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2014)
The aim of research are examining the application of cooperative learning model with CRH (Course, Review, Horray) type to improve student’s mathematical understanding ability. The research utilized a quasi experimental design. The population in this research are students in grade eight from one of junior high school in South Jakarta. As concern, the sample comprised of 32 students in CRH class (experiment group) and 34 students in conventional class (control group) which choosed by using purposive sampling technique. The problems are to improve mathematical understanding ability The quantitative analysis is used independent sample t-test, while qualitative analysis used a descriptive one. The result shows better increasing mathematical understanding ability by cooperative learning model applied CRH than by conventional teaching.